The estimation on missing daily rainfall data at Machang and Ampang station using generalized linear model / Nurul Aishah Rahman - Rahman, Nurul Aishah (2019)
A complete rainfall data plays an important role in climatological, hydrological and meteorological studies. However, the rainfall data is not always available due to several reasons such as malfunction of the instrument and power failure in recording the rainfall data. The presence of missing data could affect the continuity and consistency of the rainfall data. Thus, this study aims to estimate the missing daily rainfall data using the existing selected imputation methods, simple arithmetic average, normal ratio method, inverse distance weighting method, correlation coefficient weighting method and geographical coordinate.